2019
DOI: 10.1097/md.0000000000015582
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate, doxorubicin, and cisplatinum regimen is still the preferred option for osteosarcoma chemotherapy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 42 publications
0
55
0
Order By: Relevance
“…According to a recent meta-analysis, the methotrexate, doxorubicin, and cisplatin regimen remains the preferred option for osteosarcoma chemotherapy. 22 The most common grade 3/4 adverse event reported is neutropenia. 22 Ten of the 12 patients in our study were administered chemotherapy according to the NECO-95J protocol, which resulted in a good histological response, was comparable to induction chemotherapy, and had a favorable overall survival 23 (78.7%).…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent meta-analysis, the methotrexate, doxorubicin, and cisplatin regimen remains the preferred option for osteosarcoma chemotherapy. 22 The most common grade 3/4 adverse event reported is neutropenia. 22 Ten of the 12 patients in our study were administered chemotherapy according to the NECO-95J protocol, which resulted in a good histological response, was comparable to induction chemotherapy, and had a favorable overall survival 23 (78.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Mtx is one of the first-line chemotherapy drugs for OS, which inhibits the synthesis of tumor cells mainly by inhibiting dihydrofolate reductase (Yu et al, 2019;Zhang et al, 2020). Aln is the most important anti-bone resorber for the treatment of bone diseases (Vasikaran, 2001;Rogers et al, 2015).…”
Section: Evaluation Of Anti-tumor Effects In Vivomentioning
confidence: 99%
“…It is also capable of inducing senescence in solid tumor depending upon concentrations administered (Kozhukharova et al, 2018). In OS treatment, DOXO is administered intravenously along with other chemotherapeutic drugs including methotrexate (MAP) and cisplatinum (Yu et al, 2019). In vitro studies assessing the effect of DOXO in human OS cell lines showed that cellular metabolic activity and growth of U2OS spheroids decrease after 24 h DOXO drug exposure, following endocytosis (Baek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%